Role of Clinical Chemistry in Hemodialysis: Assessment of Biochemical Markers and Electrolyte Imbalances: Peran Kimia Klinis dalam Hemodialisis: Penilaian Penanda Biokimia dan Ketidakseimbangan Elektrolit - Al-Rubayee, Wasan T. (Indonesian Journal on Health Science and Medicine, 2024)
Background; Chronic kidney disease (CKD) and renal failure are significant global health concerns, affecting millions of individuals and contributing to high morbidity and mortality rates. Aims of the study; This study aims to assess biochemical, inflammatory, and oxidative stress markers in renal failure patients to identify biomarkers and guide therapeutic strategies. Methodology; This case-control study, conducted between January 1, 2023, and January 1, 2024, included 100 renal failure patients and 50 healthy controls, aged 35-55 years. The participants’ gender distribution was 60% male and 40% female in the patient group, and 50% male and 50% female in controls. Renal function parameters (serum creatinine, BUN, GFR, urine output) were measured using an automated chemistry analyzer. Biochemical markers (potassium, calcium, phosphorus, PTH) were assessed with an electrolyte analyzer and immunoassay techniques. Inflammatory markers (CRP, TNF-α) and oxidative stress markers (MDA, GPx) were quantified using ELISA and spectrophotometric methods. Result; This study compared 100 renal failure patients and 50 healthy controls. Age differences were significant (p=0.045), with the renal failure group being older (53.2 ± 12.5 years). Gender, occupation, marital status, and smoking history showed no significant differences. Renal function parameters revealed significant differences: serum creatinine (7.4 ± 3.2 mg/dL vs. 0.9 ± 0.2 mg/dL, p<0.001), BUN (55.2 ± 19.1 mg/dL vs. 12.3 ± 4.5 mg/dL, p<0.001), GFR (15.6 ± 8.3 mL/min vs. 95.3 ± 10.2 mL/min, p<0.001), and urine output (450 ± 230 mL/day vs. 1600 ± 200 mL/day, p<0.001). Biochemical markers like potassium, calcium, phosphorus, and PTH also showed significant differences. Inflammatory and oxidative markers (CRP, TNF-α, MDA, GPx) had notable disparities, all with significant p-values. Conclusions; This study demonstrates significant differences between renal failure patients and healthy controls in renal function, biochemical markers, and inflammation. Renal failure patients had higher serum creatinine, BUN, and phosphorus levels, along with altered potassium, calcium, and PTH levels. Elevated inflammatory markers (CRP, TNF-α) and oxidative stress markers (MDA, GPx) suggest enhanced inflammation and oxidative stress Highlights: CKD study: Renal function, biochemical, inflammatory, oxidative stress markers analyzed. Significant differences in creatinine, BUN, GFR, CRP, TNF-α observed. Results highlight inflammation, oxidative stress in renal failure patients. Keywords: Renal failure, Biochemical markers, Inflammation, Oxidative stress, Serum creatinine, Parathyroid hormone